What is a judicial decision? A brief analytic study for Peruvian civil procedural law - Cavani, Renzo (2017)
In this essay two basic legal concepts, judicial decision and adjudication, are explored in the light of the discipline of Peruvian Civil Procedure Code of 1993 (CPC). This analysis is made from an analyticdogmatic perspective, aiming to show that an adequate use of those concepts is decisive to solve practical problems, foremost in the field of the appeal.